Solvency, cash flow, and financial distress: A moderation analysis of company size - Agustina, Yumniati; Herawati, Vinola (Trigin Publisher, 2026)
This study investigates the impact of solvency and cash flow ratios on the likelihood of financial distress, while also examining the moderating effect of company size. The research focuses on firms in the property and real estate subsector listed on the Indonesia Stock Exchange (IDX) during the 2016–2020 period. Using a purposive sampling method, 57 firms were selected, resulting in 285 firm-year observations. Logistic regression analysis was employed to test the hypotheses. The results show that solvency has a significant positive effect on financial distress, indicating that higher levels of debt increase the likelihood of financial difficulties. In contrast, cash flow does not exhibit a significant influence on financial distress. Furthermore, company size fails to moderate the relationship between both solvency and financial distress, as well as cash flow and financial distress. These findings suggest that large company size does not necessarily mitigate the adverse effects of financial structure or liquidity on financial health within the property and real estate sector in Indonesia.